An empirical analysis of talent policy, executive incentive, and enterprise green technological innovation based on China’s A-share listed companies - Zhang, Yuan-Bo; Qu, Shi-You; Li, Hai-Bo; Li, Miao-Miao (Frontiers in Environmental Science, 2022)
This article studies how talent policies affect corporate technological innovation through executive incentive strategies based on signaling theory and principal-agent theory, with samples of 1,536 A-share listed companies from 2010 to 2020. The research finds that talent policy helps enterprises improve technological innovation’s level while accelerating it via improving executive compensation incentives’ level. Additionally, this effect path is more significant in high-tech enterprises and enterprises with weak solvency. The conclusions provide micro-evidence for the impact mechanism of talent policy on enterprise technological innovation and offer a scientific basis for optimizing talent policy to promote innovation-driven development strategy.